Assessing the Effectiveness of Financial Coaching: Evidence from the Boston Youth Credit Building Initiative. Issue 4 (14th August 2019) - Modestino, Alicia S.; Sederberg, Rachel; Tuller, Liana
Abstract : Since the 2008 financial crisis, there has been renewed interest in providing financial education to improve consumer financial decision making, especially among youth. Using a randomized controlled trial, we estimate the causal effects of a financial coaching program for young adults from linked individual‐level administrative credit reports and self‐reported survey responses. Within six months, the treatment group was 10 percentage points more likely to have access to credit compared to the control group. After 18 months, the average credit score was 26 points higher for the treatment group versus the control group, raising the likelihood of achieving a "good" credit rating by 8 percentage points. Consequently, the treatment group was less likely to rely on alternative financial services and paid lower interest rates on car loans. These impacts are largely driven by improvements in self‐efficacy, offering important insights for policymakers seeking to incorporate financial education into youth workforce development programs.